Combating the effects of rockbursts caused by seismically-induced shock waves - Mudau, Avhasei (My University, 2017)
Rockburst occurrences and their consequent damage remain a problem in modern mining, particularly at great depth. The problem of rockbursts has also escalated in deepcivilengineeringtunnelsduetohighlevelsofin-situstressatsuchdepths. Key advancementshavebeenmadetodatetohelpmitigatethedrasticimpactscausedby rockburstdamage,withrocksupportremainingalineofdefensetoprovidestability in rockbursting situations. There is, however, an ongoing inability of support to contain severe rockburst damage, especially conventional support systems. More than two decades ago, a support concept termed “sacriﬁcial support” was proposed as a potential additional method to help inhibit rockburst damage. The philosophy behind a sacriﬁcial support system is that, under dynamic loading conditions, support, in the form of a liner must fail (i.e. be ejected from rock surface), leaving behind, undamaged, what was once supported rock mass. It is because of this reason that this support is referred to as a sacriﬁcial support due to its ability to protect the rock from damage whilst the support itself fails. Since the inception of this support idea, it was only recently that the behaviour of support in real rockburst events manifested the sacriﬁcial behaviour in rockbursting, which warranted the need for further research. The sacriﬁcial support concept stated here is applicable in situations where the source (i.e. seismic event) of the rockburst is located remote from where rockburst damage is likely to occur. To investigate the behaviour of sacriﬁcial support, controlled laboratory experimentsbasedonthesplitHopkinsonpressurebar(SHPB)techniquewereconducted to study some aspects of dynamic rock fracturing in tension at high strain rates, and also the role a sacriﬁcial layer plays in combating dynamic rock failure (i.e. rockburst damage). To achieve this, a single Hopkinson pressure bar conﬁgured for spalling tests, comprised of a relatively long cylindrical intact rock specimen attached at the bar free end, was impacted by a striker on the opposite free end of the bar in order to generate a dynamic stress pulse responsible for spall failure upon reﬂection from the specimen free end. Different liners and/or liner combinations were then introduced at the specimen free end as sacriﬁcial support. This experimental arrangement allowed the role of, and failure mechanisms associated with, sacriﬁcial support under dynamic loading to be demonstrated, and comparisons were made with “sacriﬁcial support” behaviour observed in real rockburst events in a mine. Analysis of experimental results revealed that varying liner thickness and mechanical impedance between rock and support liner plays a signiﬁcant role in helping to limit rockburst damage. Apart from experimental investigations, numerical simulations were undertaken to further probe the behaviour of sacriﬁcial support under dynamic loading. Elastic models subjected to p-wave propagation indicated failure of the sacriﬁcial layer, manifested by ejection of the liner due to reﬂection of compressive wave at the free surface. This failure mechanism was noticed for all the liners, independent of variation in liner thickness, and wavelength characteristic of the applied wave to the model. The sacriﬁcial support method presented in this thesis presents an opportunity to further enhance safety in seismically active mines.
A thesis submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, Johannesburg, September 2017
Keywords: Rock bursts; Rock mechanics; Seismology